SEKULERITAS DAN SPRITUALITAS, MENCARI FORMAT INTEGRASI KEILMUAN DAN KONTRUKSI KURIKULUM PENDIDIKAN ISLAM - Listari Basuki; Syahril Rambe (Jurnal At-Tabayyun, 2020)
In the concept of Islamic religious education, it is important that education in human life even because of the importance of Allah promising the most glorious reward and place for believers and knowledge. Of course, it is very clear that education must be able to answer and believe human life so that human life can take place as expected. The high betrayal of the professional code of ethics, decreased productivity and increased consumption, and the high social nudity requires that education must undergo changes and construction to the curriculum in order for education to adopt dynamic and creative character.